Accuracy of Ultrasound Elastography in the Diagnosis of Thyroid Cancer in a Low-risk Population - Vidal-Casariego, A.; López-González, L.; Jiménez-Pérez, A.; Ballesteros-Pomar, M. D.; Kyriakos, G.; Urioste-Fondo, A.; Álvarez-San Martín, R.; Cano-Rodríguez, I.; Jiménez-García de la Marina, J. M. (Experimental and Clinical Endocrinology & Diabetes, 2012)
Stiffness has been associated to malignancy in prostate and breast, as well as thyroid. Ultrasound elastography objectively measures tissue elasticity, and previous studies have described it as a high sensitivity and specificity technique for the detection of malignant thyroid nodules in high-risk populations. The aim was to assess the accuracy of elastography in a population with low risk of malignancy.128 consecutive patients with nodular goiter were recruited. Elastography and ultrasound-guided fine-needle aspiration were performed. When malignancy was suspected by citology, surgery was recommended. Thyroid nodules were classified by elastography according the criteria described by Ueno, and an alternative classification. Sensitivity, specificity, predictive values, and odds ratio were calculated.Most patients were female, aged 56.1 year, with single nodule (52.0%) or multinodular goiter (45.6%), and a few thyroiditis (2.4%). The majority of nodules were mostly elastic. Fine-needle aspiration found 86% of benign nodules, 9.3% of indeterminate, and 4.7% possibly malignant. After surgery, 3 malignant nodules were confirmed, all of them being papillary carcinomas. All the malignant nodules were mostly elastic, as well as 75% of indeterminate nodules. Low values of sensitivity and specificity were found for elastic nodules being benign and hard nodules malignant.In a low-risk population for thyroid cancer, elastography lacks accuracy for the diagnosis of malignant nodules.Clinical Trials Registration Number: NCT01102127
Keywords: thyroid nodule; ultrasound elastography; fine-needle aspiration; papillary carcinoma